Longitudinal changes in motivational climate and performance anxiety among elite handball players - Abrahamsen, F. E.; Pensgaard, A. M. (International Journal of Applied Sports Sciences, 2012)
Elite athletes are under a constant demand of performing well and performance anxiety has been proved a detrimental factor for their performance. There have been few ecologically valid investigations on how changes in environment perceptions might affect self-confidence and performance anxiety. This longitudinal study, from the Achievement Goal Theory (AGT) standpoint, tried to change this lack of research. Elite female and male handball players` perceptions of the motivational climate and its effect on perceived athletic ability and performance anxiety were measured during a full handball season. Two main questions were examined: (1) Do scores on motivational climate, perceived ability, and anxiety differ between male and female elite handball players? The results only revealed gender differences in the worry scale, except in the midseason data where females perceived a significantly lower performance climate than males. (2) Are changes in perceived motivational climate across a season, associated with changes in anxiety levels? Analyses revealed that female athletes` perceptions of a dwindling mastery environment were related with a decreasing perception of athletic ability, which in turn was related with more performance worries. No associations were significant with the male players. The findings for females are coherent with AGT predictions. However, future research not to consider why there might be gender differences, because such differences will have applied consequences.